PENGARUH JUMLAH INDUSTRI, JUMLAH PENDUDUK DAN INVESTASI INDUSTRI TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI KABUPATEN SUMBAWA TAHUN 2010-2022 - Fahlia; Febriana Florensia, Juwita (Jurnal Nusa Manajemen, 2024)
This study aims to determine whether there is a variable influence of the number of industries, population and industrial investment on the absorption of industrial sector workers in Sumbawa Regency. The method used in this study is a quantitative method using multiple linear regression analysis. The result of the regresssion calculations were tested using the t test and F test with the result that the variables number of industries and industrial investment had an influence on employment in the industrial sector in Sumbawa Regency, while the population variable had no influence on employment in the industrial sector in Sumbawa Regency. However, simultaneously the variables number of industries, population, and industrial invesment jointly influence the employment of theindustrial sector in Sumbawa Regency, with a significance value of 0,001<0,05 shown, in other words the independent variables are able to explain the magnitude of the dependent variable of employment indutrial sector work